EVALUASI MODEL PEMBELAJARAN BERBASIS PROYEK DI KELAS XII SMK N 2 MEULABOH - Sadrina Sadrina (PTE FTK UIN Ar-Raniry, 2019)
Education is an important base in a nation. Thus, education is an important issue in the development plan. Education plays a very important role in developing the process of transforming Aceh into a superior Province in the next decade. Since 1956, Vocational High Schools began operating in Aceh to become a human resources printing institution that is ready to work in the world of government or industry. Therefore, Project-Based Learning (PBL) was introduced as a reliable method to be implemented in vocational schools. PBL appears as a method that focuses on student-centered learning. This research is a quantitative research that aims to find out students' perceptions of Project Based Learning in SMK N 2 Meulaboh. The sample in this study were students of class XII majoring in TIPTL, TGB, TAB, TAV, TKK, TKR and TSM, totaling 91 people. The results show that in general students believe that Project Based Learning has been running smoothly starting from the initial stage, implementation and final stage. In the initial stage, students state that the teacher starts learning with problems, gives direction and monitors the work of the student project design (min = 4.03). During the PBL implementation phase, students also mentioned that they were able to work in groups, discuss, find tools and submit projects on time (min = 3.98). Finally, at the final stage of PBL, students are confident and believe that the products produced from PBL are useful even though they are not ready to show or sell the product (min = 3.88).